TRANSLATING ??? IN JOB 2:9- A FUNCTIONALIST APPROACH - Lier, G E (Acta Theologica, 2018)
This study makes use of the Functionalist Translation approach in the translation of ??? in Job 2:9 in line with Christiane Nord’s Model of Literary Communication to demonstrate how early translators’ cognisance of the language and culture of the source text may have influenced the way they translated ??? in Job 2:9. The premise of this paper is that the translators began to render ??? in Job 2:9 conversely when they were no longer familiar with the culture of the Hebrew source text. The study aims to demonstrate that a functionalist approach in literary translation may assist with the translation of enigmatic texts in the Hebrew Scriptures to produce a target text that takes into account the source-culture inventory and appropriately communicates the translated text to the target-culture perspective.